Diagnostics of Manitischeria gen. nov., an Old-World genus of leaf-mining Tischeriidae, composed of new species and species formerly in Tischeria Zeller - Stonis, Jonas R.; Diškus, Arūnas; Solis, M. Alma; Monro, Alexandre K. (Zootaxa, 2021)
We describe a new genus, Manitischeria Diškus & Stonis, gen. nov., and five new species: Manitischeria selindica Stonis & Diškus, sp. nov., M. namibiensis Stonis & Diškus, sp. nov. from Africa, and M. brachiata Diškus & Stonis, sp. nov., M. symbolica Diškus & Stonis, sp. nov., and M. baryshnikovae Diškus & Stonis, sp. nov. from South East Asia. We discuss the diagnostics of Manitischeria gen. nov. composed of these new species and others transferred from Tischeria Zeller. Species are mostly trophically associated with Malvaceae, but also Rhamnaceae and Betulaceae. We list 18 currently known species of Manitischeria gen. nov., including M. ptarmica (Meyrick), the type species, and provide 13 new combinations and the first documentation of genitalia of some, previously little-known species. New species are illustrated with photographs or drawings of the adults, genitalia, and the leaf mines when available. We briefly discuss the use of herbarium specimens to discover lepidopteran leaf mines, host plant, and distribution data.